Synthesis and Characterization of Porous Ceramic Hollow Fibers with Nano-Molecular Size - Hussein, Hussein Qasim (Journal of Petroleum Research and Studies, 2018)
This research exhibits a method for the fabrication of nano molecular size ceramic porous hollow fibers, using the internal diffusion technique. This method is based on preparation a spinning solution consists from nano gamma alumina < 50nm in an aqueous mixture of sodium alginate, and calcium carbonate. The mixture is spun into a lactic acid coagulation bath of pH= 1.6 to achieve ionic cross-linking. The green transparent ceramic hollow fibers were dried under ventilation at ambient temperature for 48h and sintered at different temperatures 1100 oC-1350 oC for 2h. The synthesized fibers were characterized and the effect of sintering temperature on surface morphology was studied. The phase transformation from gamma to alpha was specified by x-ray diffraction, at 1100 oC a few small and sharp peaks of α-alumina started while at 1250 oC α-alumina with a highly crystalline structure was obtained. Microstructure and surface morphology of nano ceramic fibers were studied at different sintering temperatures, a homogeneous particle distribution was gained at a temperature of 1250 oC. The thermal gravimetric analysis was referred to an existence of two thermal steps occurred during thermal treatment, dehydration up to 250 oC and alginate dehydration and decomposition from 250 oC to 400 oC. The nitrogen isotherm behavior indicates to a mesoporous / macroporous substance, an appearance of type H-2 hysteresis loop. BJH adsorption and desorption average pore diameter (4V/A) 14.4408 nm and 17.7124 nm respectively. Single point surface area is 9.268 m²/g, single point adsorption total pore volume is 0.023 cm³/g. The average interior and exterior pore size by mercury intrusion were 20 nm and 50 nm respectively.